TINJAUAN HUKUM TENTANG EFEKTIVITAS PERJANJIAN SEWA MENYEWA RUMAH DI KOTA MAKASSAR (Qawanin Jurnal Ilmu Hukum, 2021)
"Legal Overview of the Effectiveness of theLease Agreement to Rent a House in Makassar City". Under the guidance ofMuhammad Rustan as Chief Advisor and Sahban as Advisor. This study aims todetermine the effectiveness of the rental agreement for renting a house inMakassar City in making agreements between home owners and tenants so asto provide legal certainty for both parties. This research uses empiricalresearch. The location of this research was carried out on Sultan AlauddinStreet, Bosowa Housing Complex, Makassar City and West Kabila Street. Typesand sources of data used are primary data and secondary data. Datacollection techniques, library research and field research. Data analysis,namely data that has been obtained both primary and secondary data willthen be processed and analyzed to produce conclusions, then presenteddescriptively.